2016
DOI: 10.5194/nhess-16-1499-2016
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution wave and hydrodynamics modelling in coastal areas: operational applications for coastal planning, decision support and assessment

Abstract: Abstract. Numerical modelling has become an essential component of today's coastal planning, decision support and risk assessment. High-resolution modelling offers an extensive range of capabilities regarding simulated conditions, works and practices and provides with a wide array of data regarding nearshore wave dynamics and hydrodynamics. In the present work, the open-source TELEMAC suite and the commercial software MIKE21 are applied to selected coastal areas of South Italy. Applications follow a scenario-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 41 publications
(41 reference statements)
1
15
0
Order By: Relevance
“…Most of the numerical models used in predictive operational oceanography allow us to reproduce and predict the hydrodynamic processes, considering regional, sub-regional, and coastal scales, but do not reach spatial resolutions lower than a few hundred metres (Samaras et al, 2016). As a consequence, difficulties are encountered when typical features of coastal engineering need to be studied on a local scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the numerical models used in predictive operational oceanography allow us to reproduce and predict the hydrodynamic processes, considering regional, sub-regional, and coastal scales, but do not reach spatial resolutions lower than a few hundred metres (Samaras et al, 2016). As a consequence, difficulties are encountered when typical features of coastal engineering need to be studied on a local scale.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, difficulties are encountered when typical features of coastal engineering need to be studied on a local scale. Reliable modelling systems that can scale down from the ocean to the coastal scale have emerged as a need and the recent tendency is to develop multiscale modelling systems, based on a multiple-nesting approach (Samaras et al, 2016). All these models have to face three difficult limitations to provide reliable results on the circulation in the basin.…”
Section: Introductionmentioning
confidence: 99%
“…T R = 2 years 1.00 8.5 260 T R = 100 years 1.70 11.0 265 gular meshes as recently applied by Samaras et al (2016) and Gaeta et al (2016). The adopted bathymetric and shoreline data result from the digitisation of nautical charts acquired from the Italian Hydrographic Institute.…”
Section: Design Waves From Nwmentioning
confidence: 99%
“…Coupled wave-2-D hydrodynamics modeling was discussed and validated in Samaras et al (2016), based on the intercomparison of the TELEMAC suite and the well-known commercial software MIKE21 by the DHI © group.…”
Section: Multiple-nesting Approach and Model Descriptionmentioning
confidence: 99%
“…The wave spectra are discretized to 16 directions, with a bandwidth of 24 • . Nonlinear energy conservative processes are included in the model setup according to the authors' experience reported in Samaras et al (2016). The model of Hasselmann et al (1973) is used for bottom friction dissipation using a constant friction coefficient.…”
Section: Field Data Collectionmentioning
confidence: 99%